MAQASHID SYARIAH SEBAGAI PARAMETER KEBERHASILAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY - Ria Nelta Febriyanti (Program Studi Ekonomi Syariah, 2023)
Corporate Social Responsibility is a company's sensitivity in looking at its surroundings, both society and the environment. The implementation of corporate social responsibility is now increasingly developing. However, unfortunately, this development is not matched by an increase in the welfare of the surrounding community. This is because there are no clear CSR success parameters from the government that must be adopted by companies. In Islamic economics, welfare cannot be measured by just looking at an increase in assets owned. However, the benchmark for prosperity is measured by maintaining five values or what is known as maqashid sharia. Maqashid sharia consists of five maintenance, namely Deen (religion), Nafs (soul), Aql (reason), Nashl (offspring), and Maal (treasure). Maqashid sharia are the five basic goals of a human being to achieve falah (prosperity). As the government's effort to achieve the 2015 MDGs program, maqashid sharia is expected to become an indicator for companies in measuring the success of their CSR. With the existence of maqashid sharia as a parameter for the success of corporate social responsibility, it is hoped that it will be able to accelerate the achievement of the goals of ongoing government programs.